Using the Root Assessment Method to Choose the Optimal Solution for Mushroom Cultivation - Trung, Do Duc; Duc, Duong Van; Bao, Nguyen Chi; Thuy, Duong Thi Thanh (Yugoslav Journal of Operations Research; Vol 35 No 2 (2025)DO - 10.2298/YJOR240115007T, 2024)
In this study, an investigation was conducted into two essential aspects of mushroom cultivation. Firstly, the selection of the best type of fertilizer out of ten different options was examined to optimize mushroom growth. The RAM (Root Assessment Method) method was used in conjunction with five different weighting methods to evaluate the alternatives. The research results revealed the two most outstanding fertilizers for mushroom cultivation. Next, the selection of the best cultivation mixture out of six proposed options was investigated. Using the same RAM method and various weighting methods, a unique and efficient mixture for mushroom cultivation was identified. This study provides valuable information for farmers and those interested in mushroom cultivation with specific and effective solutions to improve the mushroom growing and care process.